A call for a streamlined ethics review process for multijurisdictional, child health research studies. Issue 7 (19th December 2019) - Lemyre, Brigitte; Bodani, Jaya P; Doucette, Stefani; Dunn, Michael S; Louis, Deepak; Monterrosa, Luis; Mukerji, Amit; Schmölzer, Georg M; Shah, Prakeshkumar; Singh, Balpreet; Wong, Jonathan; Lacaze-Masmonteil, Thierry; et al.
Abstract: To be time and resource efficient in neonatal research and to answer clinically relevant questions with validity and generalizability, large numbers of infants from multiple hospitals need to be included. Multijurisdictional research in Canada is currently fraught with research ethics review process hurdles that lead to delays, administrative costs, and possibly termination of projects. We describe our experience applying for ethics review to 13 sites in 7 provinces for a project comparing two standard of care therapies for preterm born infants with respiratory distress syndrome. We welcome the current opportunity created by the Institute of Human Development Child and Youth Health and the Institute for Genetics, to collaboratively identify practical solutions that would benefit Canadian researchers, Research Ethics Boards, and children and families.